2002
DOI: 10.1521/aeap.14.4.81.23876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sexual Health Approach to Prevent HIV Among Low Income, Urban, Primarily African American Women: Results of a Randomized Controlled Trial

Abstract: This randomized controlled trial evaluated an innovative culturally specific sexual health intervention-targeting, but not limited to, low-income African American women-in which HIV and sexually transmitted disease prevention strategies were combined with comprehensive sexuality education. The intervention was delivered and evaluated in community-based settings to 218 participants randomly assigned to treatment or a no-treatment control group. Participants were interviewed at pretest and 3 and 9 months after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
0
28
1
2
Order By: Relevance
“…In addition, the results were dissimilar from other published studies that have found African American participants to prefer African American counselors with culturally sensitive counseling values (Robinson et al 2002;Roberts and Miller 2004;Thompson et al 1994). African American participants in the present study rated higher comfort levels for European American counselors who emphasized cultural sensitivity, as opposed to African American counselors with this counseling value.…”
Section: Race Of Counselor and Counseling Valuecontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the results were dissimilar from other published studies that have found African American participants to prefer African American counselors with culturally sensitive counseling values (Robinson et al 2002;Roberts and Miller 2004;Thompson et al 1994). African American participants in the present study rated higher comfort levels for European American counselors who emphasized cultural sensitivity, as opposed to African American counselors with this counseling value.…”
Section: Race Of Counselor and Counseling Valuecontrasting
confidence: 99%
“…Race and culture can impact sexual behavior on a number of levels, requiring the counselor's awareness of cultural issues. In one study, young African American women who reported experiences of racism were more likely to engage in sexual risk-taking behavior due to the negative impact of racism on their sexual self-concept (Robinson et al 2002). In another study, experiences of racial bias influenced high-risk sexual behavior in African Americans through their internalization of poor social attitudes, development of negative self-image, and elevated levels of perceived powerlessness (Roberts and Miller 2004).…”
Section: Counselor Valuesmentioning
confidence: 99%
“…In previous work, we have investigated the importance of specific components of the Sexual Health Model (e.g., culture, sexual anatomy and functioning, sexual health care, challenges, masturbation and fantasy, positive sexuality, etc.) in a variety of populations (Bockting, Robinson, Forberg, & Scheltema, 2005;Miner, Robinson, Hoffman, Albright, & Bockting, 2002;Robinson, Bockting, & Harrell, 2002;Robinson, Scheltema, & Cherry, 2005;Robinson, Uhl et al, 2002;Ross et al, 2001;Untiedt, 2003;Zamboni, Robinson, & Bockting, in press). …”
Section: Introductionmentioning
confidence: 99%
“…16,17 In other studies, knowledge of HIV did not necessarily reflect a decrease in engaging in HIV associated risk behaviors. [17][18][19][20][21][22] However, we noted that there were still sizeable knowledge gaps related to the methods of HIV transmission in that many respondents were concerned abut HIV transmission by methods that do not carry a risk. The reported use of condoms and regular condom use by almost two thirds of the respondents in the survey is encouraging.…”
Section: Discussionmentioning
confidence: 99%